Implementation of Good Corporate Governance in The Regional General Hospital Padang Pariaman West Sumatra - Engga Lift Irwanto; Roni Ekha Putera; Ria Ariany (Journal of Public Administration and Government, 2024)
This research was conducted with the aim of seeing the implementation of health services carried out by the Padang Pariaman Regional General Hospital institution to the community based on the concept of implementing Good Corporate Governance. The research was conducted using qualitative research methods with interviews and document data as the main source of research data, based on the premise of good corporate governance in the form of transparency, accountability, responsibility, independence, and fairness. The research was conducted because of the many complaints for Padang Pariaman Hospital to immediately improve the quality of its services. This research was conducted by researchers with qualitative research methods. The results of the study found that the implementation of the principle of transparency has been implemented by Padang Pariaman Hospital well, for both sides, there are no complaints and criticisms conveyed by the community. Then for independence has been implemented well Padang Pariaman Hospital has been able to conduct an evaluation study of the implementation of the programme in order to manage the interests of future services by implementing communication coordination and evaluation. However, the principles of accountability, responsibility and fairness have not been implemented optimally, especially for the benefit of the community as patients who use health treatment services at the Padang Pariaman Hospital.